Muscle Relaxation of the Foot Reduces Corticospinal Excitability of Hand Muscles and Enhances Intracortical Inhibition - Kato, Kouki; Muraoka, Tetsuro; Mizuguchi, Nobuaki; Nakagawa, Kento; Nakata, Hiroki; Kanosue, Kazuyuki (Frontiers in Human Neuroscience, 2016)
The object of this study was to clarify the effects of foot muscle relaxation on activity in the primary motor cortex of the hand area. Subjects were asked to volitionally relax the right foot from sustained contraction of either the dorsiflexor (tibialis anterior; TA relaxation) or plantarflexor (soleus; SOL relaxation) in response to an auditory stimulus. Single- and paired-pulse transcranial magnetic stimulation (TMS) was delivered to the hand area of the left primary motor cortex at different time intervals before and after the onset of TA or SOL relaxation. Motor evoked potentials (MEPs) were recorded from the right extensor carpi radialis (ECR) and flexor carpi radialis (FCR). MEP amplitudes of ECR and FCR caused by single-pulse TMS temporarily decreased after TA and SOL relaxation onset, respectively, as compared with those of the resting control. Furthermore, short-interval intracortical inhibition (SICI) of ECR evaluated with paired-pulse TMS temporarily increased after TA relaxation onset. Our findings indicate that muscle relaxation of the dorsiflexor reduced corticospinal excitability of the ipsilateral hand muscles. This is most likely caused by an increase in intracortical inhibition.